EFEKTIVITAS PENGGUNAAN MEDIA TELEMEDICINE BERDASARKAN HUKUM INDONESIA DAN MALAYSIA - Juni Rahmadhani Simatupang; Ardiansah; Sudi Fahmi (Fakultas Hukum, Universitas Samudra, 2023)
This study aims to examine the effectiveness of the use of telemedicine media according to the positive laws that apply in Indonesia and Malaysia. This study uses normative juridical research methods using secondary data. The results of the study show that the use of telemedicine media based on Law Number 20 of 2019 concerning the Implementation of Telemedicine Services Between Health Service Facilities is only limited to Health Service Facilities. Meanwhile in Malaysia based on the Telemedicine ACT 1997 the use of telemedicine media is only for medical practitioners who have telemedicine certificates. Conclusion in Indonesia and Malaysia have similarities and differences in the use of telemedicine media. Laws governing health care need to be updated both from data privacy laws and the use of telemedicine media. Keywords: Telemedicine; Indonesia; Malaysia